Beyond the Nation and the Daerah: Pan-Malaysianism and Ahmed Ibn Parfahn's Malayan Grandeur and Our Intellectual Revolution - Salazar, Zeus A. (Philippine Social Sciences Review; Vol. 48 Nos. 1-4 Jan-Dec 1984; Ed. Bernardita R. Churchill, 2012)
see text